2021
DOI: 10.1002/slct.202100928
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Docking Studies of Potent Urease Inhibitors Based on Benzoxazole Scaffold

Abstract: In this study, we report the synthesis, in silico molecular docking, and in vitro urease inhibition studies of a novel series of benzoxazole derivatives. The title compound in the series namely (2-(benzo[d]oxazol-2-ylthio)-1-(4-substitute-phenyl) ethan-1-one oxime was synthesized by the reaction of 2aminophenol with different kinds of intermediates in several steps through both conventional and microwave techniques.All compounds were found to have an excellent degree of urease inhibitory potential ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, most previous research studies reported that a bunch of total residues (Ala365, Met366, Ala169, His322, Cys321, Asp223, Asn168) make the hydrophobic and hydrophilic regions and the two embedded Ni 2+ ions conjointly participate a significant role by linking the critical amino acid and ligands. It was been observed that all of the most potent compounds made interaction with them in the active pocket of the urease enzyme [34,36–38] …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, most previous research studies reported that a bunch of total residues (Ala365, Met366, Ala169, His322, Cys321, Asp223, Asn168) make the hydrophobic and hydrophilic regions and the two embedded Ni 2+ ions conjointly participate a significant role by linking the critical amino acid and ligands. It was been observed that all of the most potent compounds made interaction with them in the active pocket of the urease enzyme [34,36–38] …”
Section: Resultsmentioning
confidence: 99%
“…The inhibitors of the urease can be categorized into two classes; substrate like inhibitors (hydroxyurea, hydroxamic acids) and mechanism based inhibitors (phosphorodiamidates). During the past years, extensive research has been done on the design and development of urease inhibitors such as hydroxamic acids, [51] urea and thiourea derivatives, [52] polyphenols, [53] isoniazids, [54] catechol-based inhibitors, [55] flavonoids, [56] coumarins, [57] indoles, [58] chalcones, [59] thiazoles, [60] thiazolidinones, [61] benzothiazoles, [62] benzoxazoles, [63] benzimidazoles, [64] barbituric acid and thiobarbituric acid derivatives, [65] quinazolinones, [66] triazoles, [67] phosphoramides, [68] sulfonamides, [69] thiadiazoles, [70] oxadiazoles, [71] thiosemicarbazones, [72] diamides, [73] benzenesulfonohydrazides [74] and many more. The most effec-tive inhibitors of urease cited in the literature are phosphorodiamide and phosphorotriamide derivatives such as NBPT (N-n butylthiophosphorictriamide), PPD (phenylphosphorodiamidate), NBPTO (N-n butylphosphorictriamide and flurofamide (Ndiaminophosphoryl-4-fluorobenzamide) [75] (Figure 6).…”
Section: Inhibitors Of Ureasementioning
confidence: 99%
“…Jack bean urease inhibitory activity and kinetic studies on the synthesized compounds and thiourea were examined based on previously published studies. 14,[27][28][29][30] Thiourea (Sigma-Aldrich) was used as the standard inhibitor. The urease inhibition percentage was calculated as follows where OD control is the activity of the enzyme without the compound/standard and OD compound is the activity of the enzyme with the compound/standard at different concentrations.…”
Section: In Vitro Urease Inhibition Assay and Kinetic Studiesmentioning
confidence: 99%
“…Jack bean urease inhibitory activity and kinetic studies on the synthesized compounds and thiourea were examined based on previously published studies. 14,2730 Thiourea (Sigma-Aldrich) was used as the standard inhibitor. The urease inhibition percentage was calculated as follows…”
Section: In Vitro Urease Inhibition Assay and Kinetic Studiesmentioning
confidence: 99%